Rediscovering Paul : an introduction to his world, letters, and theology - Capes, David B.; Reeves, Rodney, 1957-; Richards, E. Randolph (Ernest Randolph) (Downers Grove, Illinois. IVP Academic, 2017)
"Drawing on the best of contemporary scholarship, and with language shaped by teaching and conversing with today's students, Rediscovering Paul is a textbook that has passed the test. Now in a reworked edition, it's better than ever. There are fresh discussions of Paul's letter writing and how these letters were received in the churches, new considerations of pseudonymity and the authenticity of Paul's letters and updated coverage of recent developments in interpreting Paul. From Paul's conversion and call to his ongoing impact on church and culture, this second edition of Rediscovering Paul comes enthusiastically recommended." -- Back cover
Introduction: The Challenges of Rediscovering Paul -- Rediscovering Paul in His World -- The Christophany -- Paul, the Letter Writer -- The Itinerant Paul: Galatians -- The Itinerant Paul: The Thessalonian Letters -- The Itinerant Paul: The Corinthian Letters -- The Itinerant Paul: Romans -- The Imprisoned Paul -- The Pastoral Paul -- Paul's Theology and Spirituality -- Paul's Legacy -- Paul's Letters to Our Churches.
Includes bibliographical references and index.
Keywords: Paul, -- the Apostle, Saint; Bible. -- Criticism, interpretation, etc; Bible. -- Theology; Criticism, interpretation, etc